AKIBAT HUKUM PELAKSANAAN JUAL BELI DIBAWAH TANGAN ATAS TANAH YANG BELUM BERSERTIFIKAT DI DESA DASAQ KECAMATAN MUARA PAHU KABUPATEN KUTAI BARAT - Alda Aulia (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTOne of the principles of a rule of law, namely the existence of a guarantee of legal certainty, especially in the field of land, to implement this principle the Basic Agrarian Law (UUPA) Number 5 of 1960 which regulates land ownership and use rights in Indonesia, is based on the provisions that applies if there is a transfer of rights over land such as sale and purchase, to obtain legal certainty the land must be registered, this is as regulated in the Basic Agrarian Law article 19 and article 23 paragraph (1) in conjunction with Article 37 paragraph (1) government regulation number 24 1997. land certificate as proof of ownership. However, in reality there are still uncertified land buying and selling practices. Usually this practice is carried out on the basis of mutual trust through a receipt or only using evidence as limited as a letter made in the village, which is called an underhand sale and purchase. The practice of buying and selling under the hands is often carried out, especially by people in Dasaq Village. The research method used in this research is legal research methods. The type of research used is empirical legal research. The problem approach used is the statue approach and the conceptual approach. This research was conducted in Dasaq Village, Muara Pahu District, West Kutai Regency. From the results of the research, it was found that in this village, there were still a lot of underground selling and buying practices because the land owned by the community in the village generally did not have a certificate or had not been registered. Underhand land sale and purchase transactions, among others, are based on mutual trust, through a receipt and through the Village Head based on a sale and purchase letter. The legal consequence of the underhand sale and purchase of uncertified land in Dasaq Village is that there is no legal certainty of the transfer of rights to the land as regulated in the Basic Agrarian Law because it has not been registered to obtain a certificate as proof of ownership of land rights.keywords: buying and selling under the hands, legal consequences, land registration, legal certainty.